2013
DOI: 10.1021/es305257s
|View full text |Cite
|
Sign up to set email alerts
|

Pu(V) and Pu(IV) Sorption to Montmorillonite

Abstract: Plutonium (Pu) adsorption to and desorption from mineral phases plays a key role in controlling the environmental mobility of Pu. Here we assess whether the adsorption behavior of Pu at concentrations used in typical laboratory studies (≥10(-10) [Pu] ≤ 10(-6) M) are representative of adsorption behavior at concentrations measured in natural subsurface waters (generally <10(-12) M). Pu(V) sorption to Na-montmorillonite was examined over a wide range of initial Pu concentrations (10(-6)-10(-16) M). Pu(V) adsorpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
105
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(116 citation statements)
references
References 54 publications
10
105
1
Order By: Relevance
“…The Fe(II)/Fe(III) redox couple can stabilize the oxidation state of Pu, since Fe(II) typically oxidizes before Pu(IV), while Fe(III) is typically reduced before Pu(IV). This couple also affects environmental Pu transport mechanisms, since Pu(IV) is relatively insoluble in water, but forms PuO 2 colloids [9,10] and sorbs to colloidal minerals [79][80][81]. The encasement of Pu into macroscale glassy matrices, however, may reduce the probability of initial colloid formation, and serve to inhibit the transport of actinides, as observed in waste vitrification studies.…”
Section: To Fe(iii) and Corresponding U(vi) Reduction To U(iv) It Imentioning
confidence: 99%
“…The Fe(II)/Fe(III) redox couple can stabilize the oxidation state of Pu, since Fe(II) typically oxidizes before Pu(IV), while Fe(III) is typically reduced before Pu(IV). This couple also affects environmental Pu transport mechanisms, since Pu(IV) is relatively insoluble in water, but forms PuO 2 colloids [9,10] and sorbs to colloidal minerals [79][80][81]. The encasement of Pu into macroscale glassy matrices, however, may reduce the probability of initial colloid formation, and serve to inhibit the transport of actinides, as observed in waste vitrification studies.…”
Section: To Fe(iii) and Corresponding U(vi) Reduction To U(iv) It Imentioning
confidence: 99%
“…The affinity of Pu(IV) to mineral surfaces is substantially greater than that of Pu(V), and this has been attributed to their difference in effective charge (11). However, it has been shown that Pu(V) can be reduced to Pu(IV) and even Pu(III) on a range of mineral surfaces, leading to a congruence in the apparent sorption behavior of Pu(IV) and Pu(V) (5). At high concentrations (Ͼ10 Ϫ8 Ϯ 1 M), Pu(IV) hydrolyzes to form Pu(IV) oxide precipitates (4,12).…”
mentioning
confidence: 99%
“…Many studies argued that Pu(V) aq has weak affinity for mineral surfaces (an implication of higher mobilization). An interpretation that slow reduction of Pu(V) aq to Pu(IV) aq , which has a higher tendency to complex with ≡X-OH sites (X = Al, Fe, and Mn), was usually given (Roberts et al, 2008;Begg et al, 2013;Powell et al, 2014). Instead, much lower mobilization of Pu(V) aq was observed in our transport experiments.…”
Section: Accepted Manuscriptmentioning
confidence: 55%